PENANDA FUNGSI DAN MEDIA PROMOSI DI KORIDOR JALAN HAYAM WURUK, DENPASAR - Aritama, Anak Agung Ngurah (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 3 (2016): Oktober 2016DO - 10.24843/JRS.2016.v03.i03.p04, 2016)
The installation of signage serves numerous functions and is now an integral part of commercial development, transport and other urban uses. In addition it is frequently located to promote information driven by political, economic, social and directional purposes. The phenomenon raised within this article is the uncontrolled presence of urban signage to a level that ruins the image of a town, as is observed when one walks along the Hayam Wuruk Corridor of Denpasar Kota. The article focuses on the comprehension of factors leading to the overall lack of control that generates such chaotic effects. In achieving this objective, the following article is organized into four sub sections. First, the abstract briefly explains the structure and organization of the presentation. Second, the introduction outlines the overall context of the problem and the choice of the Hayam Wuruk Corridor as the selected case study. The third section contains an explanation of the meaning, function and type of signage found along the Corridor. The fourth section demonstrates in a great detail, the underlying factors in the organization of urban signage and the criteria that allow functional requirements to be met without ruining environmental considerations. Thus the urban image the Denpasar Kota is keen to maintain can be respected. The last section synthesizes key elements in the paper and suggests potential outcomes. Keywords: urban signage; urban image; type, meaning and function of the urban signage. Abstrak Seiring perkembangan waktu, keberadaan penanda fungsi dan media promosi pada koridor kawasan menimbulkan berbagai permasalahan terkait visual dan wajah kota. Begitu pula yang terjadi pada koridor Jalan Hayam Wuruk di Kota Denpasar. Koridor jalan ini merupakan salah satu koridor dengan aktivitas komersial dan perdagangan yang cukup sibuk. Berdasarkan hasil pengamatan, kondisi penanda fungsi dan media promosi pada koridor tersebut tidak tertata dengan baik. Studi ini bertujuan untuk mengidentifikasi dan menemukan faktor-faktor yang menyebabkan sejumlah permasalahan tersebut. Pendekatan yang dilakukan melalui metode kualitatif dengan didukung oleh studi kepustakaan yang relevan dengan topik penelitian. Artikel ini terdiri atas empat sub pokok bahasan. Bagian abstrak memuat poin-poin penting mengenai artikel ini. Bagian kedua memaparkan pokok-pokok permasalahan serta gambaran umum mengenai tiga segmen dari koridor yang diteliti. Bagian ketiga berisikan penjelasan mengenai pengertian, fungsi dan jenis penanda fungsi dan media promosi; dan faktor-faktor yang menyebabkan permasalahan pada penanda fungsi dan media promosi tersebut. Bagian keempat memuat kesimpulan hasil studi.
Keywords: penanda fungsi, citra kota, tipe, makna, dan fungsi penanda kota